ME AJUDEM POR FAVOR É PRA AMANHAAAAAA!!!!
Anexos:
![](https://pt-static.z-dn.net/files/d83/be78a8ecc2d4c3715bf349b270015fe0.jpg)
Soluções para a tarefa
Respondido por
0
Resposta:
Conforme abaixo.
Explicação passo a passo:
Em todos os casos permutamos/trocamos "y" por "x".
a) y = 5x - 3
x = 5y - 3 ⇒ y = (x + 3)/5
b) y = x + 24
x = y + 24 ⇒ y = x - 24
c) y = 3x - 24x + 3 (x ≠ -34)
y = -21x + 3
x = -21y + 3 ⇒ y = (x - 3)/-21 ⇒ y = - (x - 3)/21 (y ≠ -34)
d) y = x³
x = y³ ⇒ y³ = x ⇒ y = ∛x
Perguntas interessantes
Biologia,
7 meses atrás
Matemática,
7 meses atrás
Geografia,
7 meses atrás
Química,
7 meses atrás
Matemática,
1 ano atrás